Toxicity of hydroxyurea in the treatment of sickle cell anemia - Marçal, Pedro Henrique Ferreira (2022)
Sickle cell anemia is a hereditary disease, characterized by the alteration of red blood cells, making them look like a sickle, hence the name sickle cell. In Brazil, it affects about 8% of the black population, but due to the intense miscegenation historically occurred in the country, it can also be observed in white or brown people. The work was developed with the general objective of analyzing the characteristics of sickle cell anemia and the toxicity presented by hydroxyueria in its treatment. The work was elaborated through a bibliographic review in books and articles selected through searches in databases and books websites, the period of the researched material covers the works published between the years 2010 and 2019. Hydroxyurea is now one of the drugs most used in the treatment of sickle cell anemia for being able to increase the production of another type of hemoglobin, known as fetal hemoglobin (more present during the uterine life). High levels of fetal hemoglobin decrease the polymerization of defective red cells and reduce the risk of vaso-occlusion. Like any chemotherapy drug, however, hydroxyurea has adverse effects. Hydroxyurea represents the first drug option for patients experiencing moderate to severe clinical conditions. However, it is important to highlight the incidence of clinical improvement in all patients who use this drug.